Titan cell formation is unique to Cryptococcus species complex - Dyląg, Mariusz (Virulence, 2020)
Members of the Cryptococcus species complex stand out by unique virulence factors that allowed evolutionary transition to pathogenesis. Among the factors contributing to cryptococcosis is a morphological transformation into giant (Titan) cells. It remains unclear whether species outside of the C. neoformans/C. gattii species complex are capable of titanization. We utilized two recently developed protocols that allow obtaining Titan cells in vitro to test if titanization occurs in non-C. neoformans/C. gattii species. We find that none of the tested strains, representing 10 species of basidiomycetous yeasts and the ascomycetous yeast Saccharomyces cerevisiae, undergo significant titanization under conditions that promote robust Titan cell formation in C. neoformans/C. gattii species complex. C. terreus formed occasional enlarged cells through a mechanism potentially similar to that of titanization. Our findings suggest that titanization is a rare phenomenon among basidiomycetous yeasts that occurs mostly in members of the C. neoformans/C. gattii species complex.